Time to restart: A comparative compilation of triage recommendations in dentistry during the Covid −19 pandemic - Mousumi Goswami; Sakshi Chawla (Elsevier, 2020)
Background: The novel coronavirus (COVID-19) pandemic has become a enormous challenge for the health care facilitators. It has significantly affected the dental professionals in their clinical practices, hospitals and even dental schools. Due to the risk of cross - infection involved within in the dental setting, the dental professional is even scared to provide emergent treatment for a patient. Aim: The aim of this comparative review is to throw light on the essential knowledge that a clinician must acquire before triaging a patient, understanding the case definition of COVID-19 and preparedness required before planning to re-open the dental practices. Methodology: The updated database obtained from various governmental and non-governmental official webpages were rapidly analysed up till May 31, 2020. Conclusion: This compilation of recommendations and guidance laid by various authorities across the world will function as a foundation for safer dental practice within the future.